2007
DOI: 10.1029/2007jd008464
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical characteristics of nascent aerosols produced by bursting bubbles at a model air‐sea interface

Abstract: [1] Breaking waves on the ocean surface produce bubbles that, upon bursting, inject seawater constituents into the atmosphere. Nascent aerosols were generated by bubbling zero-air through flowing seawater within an RH-controlled chamber deployed at Bermuda and analyzed for major chemical and physical characteristics. The composition of feed seawater was representative of the surrounding ocean. Relative size distributions of inorganic aerosol constituents were similar to those in ambient air. Ca 2+ was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
461
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(518 citation statements)
references
References 79 publications
53
461
4
Order By: Relevance
“…The Bubbler consisted of a large glass cylinder filled with seawater, and bubbles were produced by flowing zero air through two sets of ceramic frits (fine and coarse) or by dropping jets of seawater on to the model seawater surface. 21 The continuously regenerated seawater surface contained ambient seawater constantly pumped by the R/V Atlantis. The bubbles burst at the seawater surface, which lofted the resulting aerosol into a continuous air stream.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The Bubbler consisted of a large glass cylinder filled with seawater, and bubbles were produced by flowing zero air through two sets of ceramic frits (fine and coarse) or by dropping jets of seawater on to the model seawater surface. 21 The continuously regenerated seawater surface contained ambient seawater constantly pumped by the R/V Atlantis. The bubbles burst at the seawater surface, which lofted the resulting aerosol into a continuous air stream.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Studies of oceans and lakes have shown that aerosols may be produced by bubble bursting and breaking waves, 43,44 and such processes may be active, though at smaller scale, in a sewer system. To the best of our knowledge, this study is the first to investigate the aerosol size distribution produced by converging sewer pipes.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus and norovirus concentrations as high as 2.27 × 10 6 genome copies m -3 and 1.42± 1.14 × 10 3 genome copies m -3 , respectively, have been reported. 42,43 Based on the current literature, it appears that airborne concentration of EBOV at a WWTP may be affected by the treatment process, the concentration of EBOV in wastewater, and the sampling location.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
“…2,5,8 The organic to inorganic ratio within individual SSA particles has been shown to vary as a function of particle size, containing up to 80% organic carbon by mass. 17 While the majority of supermicrometer SSA particles contain mostly sea salt (i.e., Na + , K + , Mg 2+ , Ca 2+ , and Cl − ), SSA particles become more enriched with organic species relative to inorganic species as particle diameter decreases down to submicrometer sizes. This trend has been shown in the average bulk aerosol composition as well as at the single particle level.…”
Section: ■ Understanding the Influence Of Interfacial Interactions Anmentioning
confidence: 99%